Impacto de la composición de las importaciones, exportaciones y diversificación de las exportaciones sobre el crecimiento económico en Latinoamérica - Quispe Delgado, Ana Milagros (2023)
Economic growth is investigated in relation to the main determinants of foreign trade: import composition, export composition and export diversification. With a sample of 19 countries for the period 2000-2018, using a Generalized Methods of Moments (GMM) panel data model, which reveals a positive significance of the composition of imports and the composition of exports over the economic growth. The first case is explained by the positive significance related with the acquisition of capital goods, and, in the second, by its positive impact of the exports of high technology goods, the commercial opening and the content of national value within them. Finally, export diversification failed to have any impact on economic growth due to the lack of uniformity in the application of this measure in the Latin American region. The application of technology in foreign trade, as well as the level of material and human resources used, also achieved significant results on economic growth and productivity.